Hypercontractile cardiac phenotype in mice overexpressing the regulatory subunit PR72 of protein phosphatase 2A - Herting, Julius R.; König, Jule H.; Hadova, Katarina; Heinick, Alexander; Müller, Frank U.; Pauls, Paul; Seidl, Matthias D.; Soppa, Carolina; Kirchhefer, Uwe (Frontiers in Cardiovascular Medicine, 2023)
Background: The activity, localization, and substrate specificity of the protein phosphatase 2A (PP2A) heterotrimer are controlled by various regulatory B subunits. PR72 belongs to the B'' gene family and has been shown to be upregulated in human heart failure. However, little is known about the functions of PR72 in the myocardium.Methods: To address this issue, we generated a transgenic mouse model with heart-specific overexpression of PP2A-PR72. Biochemical and physiological methods were used to determine contractility, Ca 2+ cycling parameters, and protein phosphorylation.Results: A 2.5-fold increase in PR72 expression resulted in moderate cardiac hypertrophy. Maximal ventricular pressure was increased in catheterized transgenic mice (TG) compared to wild-type (WT) littermates. This was accompanied by an increased shortening of sarcomere length and faster relaxation at the single-cell level in TG. In parallel with these findings, the peak amplitude of Ca 2+ transients was increased, and the decay in intracellular Ca 2+ levels was shortened in TG compared to WT. The changes in Ca 2+ cycling in TG were also evident from an increase in the full duration and width at half maximum of Ca 2+ sparks. Consistent with the contractile data, phosphorylation of phospholamban at threonine-17 was higher in TG hearts. The lower expression of the Na + /Ca 2+ exchanger may also contribute to the hypercontractile state in transgenic myocardium.Our results suggest that PP2A-PR72 plays an important role in regulating cardiac contractile function and Ca 2+ cycling, indicating that the upregulation of PR72 in heart failure is an attempt to compensate functionally.